PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PROSES PEMBELAJARAN PESERTA DIDIK PADA MATA PELAJARAN IPS - RAKHMAN, AKHMAD; Handayani, Yeni; Bakhtiar, Ahmad (Jurnal Lingkar Mutu Pendidikan, 2024)
The aim of this research is to determine the implementation of the jigsaw type cooperative learning method in an effort to increase students' interest in learning in social studies subjects in Class VI MI Mutmainnatul Qulub. The research method used is a qualitative descriptive research method. This research technique uses observation, interviews and documentation. The results of this research show that this method makes students more active in the learning process compared to applying the lecture method. Apart from that, the application of the jigsaw method can increase students' sense of responsibility because students have quite an important role in completing their group assignments.